2016
DOI: 10.1146/annurev-micro-102215-095431
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomics and the Human Virome in Asymptomatic Individuals

Abstract: High-throughput sequencing technologies have revolutionized how we think about viruses. Investigators can now go beyond pathogenic viruses and have access to the thousands of viruses that inhabit our bodies without causing clinical symptoms. By studying their interactions with each other, with other microbes, and with host genetics and immune systems, we can learn how they affect health and disease. This article reviews current knowledge of the composition and diversity of the human virome in physiologically h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(93 citation statements)
references
References 116 publications
5
87
0
1
Order By: Relevance
“…In a typical human with 10 12 nucleated cells, it is estimated that there are 10 15 virions and 10 13 bacteria (1, 2). In the past, only the components of the microbiome that could be directly visualized or grown in culture were readily appreciated (3).…”
Section: Introductionmentioning
confidence: 99%
“…In a typical human with 10 12 nucleated cells, it is estimated that there are 10 15 virions and 10 13 bacteria (1, 2). In the past, only the components of the microbiome that could be directly visualized or grown in culture were readily appreciated (3).…”
Section: Introductionmentioning
confidence: 99%
“…A thorough review has been published recently [9]. Many viruses are present in peripheral blood—in particular, members of the Herpesviridae and Anelloviridae families are identified in the absence of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Metagenomic studies also lead to the identification of novel RNA viruses—for example the identification of two rhabdoviruses [13]. Other viral sequences in the blood of healthy individuals are related to members of the Picornaviridae, Poxviridae, Flaviviridae, and Phycodnaviridae families (reviewed in [9]). Finally, a number of viruses, prominently retroviruses, are integrated in the human genome as provirus, while others may integrate occasionally or accidentally [14].…”
Section: Introductionmentioning
confidence: 99%
“…Annelloviruses are the most prevalent family [4], and metagenomics studies have identified a great degree of genetic diversity within this group [5, 6], including TTV which are separated into 39 genotypes and infect the majority of humans without any presentation of symptoms. Other viruses found in the blood of the healthy and asymptomatic populations are members of the Picornaviridae, Poxviridae, Flaviviridae, rhabdoviruses and Phycodnaviridae families [7, 8]. Recently, in a study using NGS to analyze the blood of 8,240 individuals without any symptoms of infectious diseases [4], it was reported that 94 viral species were identified, of which 19 were found in 42% of participants.…”
Section: Metagenomics In Human Bloodmentioning
confidence: 99%